EXPLORING VOCATIONAL COMMUNITY CENTERS (VCC, S) ROLE IN WOMEN SOCIO-ECONOMIC EMPOWERMENT - Irfan Javed; Dr. Sumaera Mehmood (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of this study was to examine the impact of vocational community centers (VCCs) on women’s socioeconomic empowerment. Women’s social empowerment and financial autonomy are the main study topics at VCC. The study population consisted of the Sialkot Vocational Community Centers. A deliberate sampling technique was used to select four VCCs in Sialkot City (Cantt). The single case study (holistic) technique was used to address the research subjects of the study. Audio-recorded observations, pictures taken during the events, records inspection (including old documents and artifacts), and unstructured staff and trainee interviews were all used to collect the data. The data underwent manual thematic analysis. The study’s conclusions revealed that women’s development is influenced by several factors, such as their financial autonomy, growing confidence, capacity for wise financial decision-making, and engagement in home finances. Proficiency in problem-solving, critical thinking, and craftsmanship was gained. Ultimately, these skills enabled women to gain greater financial and social influence. It proved how important these facilities are and how important it is that they be established all over Pakistan, especially in the remote and inaccessible areas. Through these institutions, the impact can be increased by mainstreaming women, who make up the majority of our population and are typically less educated, which will increase our GDP and capital.